New species in Gymnocalycium: a call for common sense - Demaio, Pablo Horacio (2014)
The proper delimitation of plant species is far away from being an issue restricted to debateamong professional botanists. Topics like teaching and communication about biodiversity,ecological and biogeographical research, and conservation and management of biologicalresources all depend on the precise identification of species. The more precisely and exactlydiagnosed a species is, the easier it will be to teach about it, to communicate its particularfeatures, to elaborate conservation policies.